Improving the Model of Long-term Technological Update of Power System Components - Denysov, Viktor; Zaporozhets, Artur; Nechaieva, Tetiana; Shulzhenko, Sergii; Derii, Volodymyr (General Energy Institute of the National Academy of Sciences of Ukraine, 2023)
An improved model of mathematical programming is proposed for the study of directions and optimal parameters of the technological renewal of energy system elements operating in energy associations, for the distant perspective and taking into account the perspectives of these elements. The model is a combination and, at the same time, a separate case of two models: a model of a hierarchical controlled quasi-dynamic system and a stochastic quasi-dynamic model of the economic and technological impact of the life cycle of innovative technologies. The main difference of the proposed improved model is the explicit consideration of the influence of economic and technological indicators of the development of the national economy and production, presented in the form of stochastic quasidynamic functions. The conducted test calculations confirm the adequacy of the proposed model, the perspective of applying this approach and further development of the model to achieve the necessary levels of detail in the forecast scenarios of the development of energy systems of Ukraine. The performed test calculations made it possible to obtain numerical estimates of the potential that can be achieved by improving the model of long-term technological renewal of power system components. Consideration of the influence of economic and technological indicators of the development of the national economy and production in the form of stochastic quasi-dynamic functions expands the tools and possibilities of obtaining high-quality predictive scenarios of the development of energy systems in Ukraine. The use of efficiency coefficients LCOE, LCOS and LACE, which are widely used in modeling the development of energy systems, increases the quality of the conclusions obtained. Examples of calculations of values of parameters of power system components under different modes of use are given.